1981
DOI: 10.1104/pp.67.5.969
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Proteases in Wheat and Corn Mesophyll Protoplasts

Abstract: proteolytic activity was associated with the chloroplasts of wheat (16). However, the intactness of the chloroplasts in this study was questionable. Much better methods are now available for the isolation of protoplasts (3, 5) and chloroplasts (13) from cereal leaves. Using these methods and a modification of the techniques for isolating plant vacuoles (14, 15), we have studied the localization of RuBPCase2 degrading enzymes in the mesophyll protoplasts of wheat and corn leaves. MATERIALS AND METHODS Plant Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 6 publications
3
54
0
Order By: Relevance
“…1). A good yield of intact chloroplasts was obtained (peak fractions (10)(11), with only a trace of broken chloroplasts (fractions [17][18]. Although considerable quantities of mitochondria and peroxisomes were occluded within the intact chloroplast band, chloroplast-free zones of peroxisomes (fractions 5-8) and mitochondria (fractions 13-16) were also located in the gradient.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…1). A good yield of intact chloroplasts was obtained (peak fractions (10)(11), with only a trace of broken chloroplasts (fractions [17][18]. Although considerable quantities of mitochondria and peroxisomes were occluded within the intact chloroplast band, chloroplast-free zones of peroxisomes (fractions 5-8) and mitochondria (fractions 13-16) were also located in the gradient.…”
Section: Resultsmentioning
confidence: 91%
“…Characterization of these enzymes (5,15,22,29) has shown that, despite their common role in protein breakdown, they have few similarities with respect to the conditions required for optimal in vitro activity. These differences, particularly differences in optimum assay pH, have led to suggestions of enzyme compartmentalization as a means of regulating protein degradation, since the plant cell contains a number of localized pH zones by virtue of its various organelles.Although acid proteinases are known to be localized in leaf vacuoles (3,11), no other peptide hydrolases have been reported there. Carboxypeptidase activity has been located in protein bodies from the cotyledons of germinating mung beans (7,27) and in vacuoles prepared from the endosperm tissue of 4-d-old castor bean seedlings (18) but has not been reported in vacuoles isolated from leaf tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2). To avoid possible adverse effects on the surface proteins of the protoplast by proteases from the cell wall digestion enzyme mixture (15), 0.05% BSA and 10 mM DIFP, a specific inhibitor for fungal serine proteases (15), were added to the digestion enzyme mixture.…”
mentioning
confidence: 99%
“…Beside this, mRNAs encoding for cysteine proteases were increased or were retained during senescence (Hensel et al 1993;Lohmann et al 1994;Smart et al 1995). It has been shown that Rubisco degrading proteases exist in the vacuole (Lin and Wittenbach 1981;Thayer and Huffaker 1984;Bhalla and Dalling 1986). Yoshida and Minamikawa (1996) suggested the involvement of at least two proteases in the degradation of purified Rubisco by vacuolar lysates.…”
Section: Introductionmentioning
confidence: 99%